Azhari, Ainul STRATEGI ASATIDZ DALAM MEMOTIVASI SANTRI PEMBAHASAN BAHSUL MASAIL DI PONDOK PESANTREN ARRISALAH KOTA TANGERANG - Azhari, Ainul; Jalil, Dul (Universitas Islam Syekh-Yusuf, 2022)
This study examines the strategies used by the asatidz (Islamic teachers) to enhance students' motivation in participating in bahsul masail activities at Ar-Risalah Islamic Boarding School in Tangerang City. Using a qualitative approach, data were collected through observation, interviews, and documentation. The findings indicate that the strategies include discussion-based methods, jidalah (debate), lectures, the wahdah method, disciplinary actions, and competitions or exams. Challenges faced include lack of student interest, boredom, health issues, and difficulty recalling religious texts. As a result, student motivation increased, many achieved awards, and the boarding school gained greater trust from the community.